Analysis of Drowsiness with Karolinska Sleepiness Scale and Heart Rate while Driving with Three Stage Road Difficulty Using Driving Simulator - Winda Halim; Anggie Ervany Haryono (OPSI, 2022)
The most dominant factor causing traffic accidents is the human factor, such as sleepy driver. Other distraction factors that can cause traffic accidents is the use of cell phones. This experiment was conducted to prove this by using a driving simulator. The experimental design will be divided into 3 stages, starting from stage 1 (easy), stage 2 (moderate), and stage 3 (difficult). This study was measured using subjective measurements using the Karolinska Sleepiness Scale (KSS) method, and objective measurement by measuring heart rate (bpm), and recording driving error data. The data collected will be processed using the Two Way Anova method to find the influencing factors. The results of the test based on subjective data there are differences in stage 3 where respondents are more awake. Meanwhile, based on objective data on heart rate measurements, there are differences between the pretest stage with stages 2 and 3. If based on driving errors, stage 1 is different from stages 2 and 3. Based on the results of data processing, it is obtained that road conditions that have a high density can increase driver alertness, then the use of mobile phones has a major influence on the occurrence of driving errors.